PENGARUH BUDAYA ORGANISASI DAN GAYA KEPEMIMPINAN TERHADAP KINERJA KARYAWAN DENGAN MOTIVASI KERJA SEBAGAI VARIABEL MODERASI - Luluk Ulil Afidah, Djoko Suseno & Setyaningsih Sri Utami (Universitas Slamet Riyadi, 2017)
The purpose of this study was to analyze: the effect of organizational culture,leadership style and work motivation on employee performance and to analyze theinfluence of organizational culture and leadership style on employee performance aremoderated by the work motivation. This study is a survey on employees PDAMSurakarta. The research sample as many as 67 people with a proportional randomsampling technique. Data collection technique used questionnaire and literature. Datawere analyzed used multiple linear regression, t-test, F, coefficient determination andtest the absolute difference. The results showed that organizational culture has asignificant effect on employee performance. Leadership style has a significant effect onemployee performance. Work motivation has a significant effect on employeeperformance. Work motivation moderating the effect of organizational culture onemployee performance. Work motivation does not moderate the effect of leadership styleon employee performance.Keywords: organization culture, leadership style, work motivation, performance